2019
DOI: 10.1002/nop2.258
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of health concerns, teamwork, leadership and knowledge transfer during an Ebola outbreak in West Africa

Abstract: Aim To describe nurses’ experiences of health concerns, teamwork, leadership and management and knowledge transfer during an Ebola outbreak in West Africa. Design The study has a qualitative descriptive design. Methods The 44 nurses who had worked in an Ebola Treatment Centre in Kenema in 2014 and 2015 were invited by email to respond to a questionnaire. The qualitative, open‐ended answers were analysed using a thematic analysis. Data have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…To support healthcare workers, many facilities have now initiated staff debriefings and are offering other psychological support services. During the Ebola virus disease outbreak, it was reported that provision of staff debriefings and other support services was critical for the safety and well-being of staff and helped to reduce distress and anxiety [65] , [66] . While the majority of respondents in our study did not use these services, a handful from each emergency clinician group did state that they found the staff debriefings to be ‘slightly to moderately useful’.…”
Section: Discussionmentioning
confidence: 99%
“…To support healthcare workers, many facilities have now initiated staff debriefings and are offering other psychological support services. During the Ebola virus disease outbreak, it was reported that provision of staff debriefings and other support services was critical for the safety and well-being of staff and helped to reduce distress and anxiety [65] , [66] . While the majority of respondents in our study did not use these services, a handful from each emergency clinician group did state that they found the staff debriefings to be ‘slightly to moderately useful’.…”
Section: Discussionmentioning
confidence: 99%
“… Evans, 2004 ) and female leaders to more frequently use the prestige strategy (cf. Holmgren et al, 2019 ). Indeed, female leaders in a forager-horticulturalists society in Ethiopia showed high prestige but low dominance, whereas male leaders were high on both prestige and dominance ( Garfield and Hagen, 2020 ).…”
Section: Assessing the Evidence For The Sexually Dimorphic Leadershipmentioning
confidence: 99%
“…More recently, during a MERS (Middle East Respiratory Syndrome, MERS-CoV) outbreak in 2012 successful management was retrospectively identified to hinge on teamwork, collective leadership and collaborative management (Al Knawy et al, 2019). Finally, experience during the Ebola Virus Disease (EVD) outbreak in 2014 highlighted the importance of team training among healthcare workers for clarifying roles, responsibilities, and rules of engagement under conditions of extreme pressure (Holmgren et al, 2019). The extent to which lessons learned from past healthcare emergencies have been applied to current health service responses to COVID-19 remain to be seen.…”
Section: Learning About Interprofessional Working From Past Pandemicsmentioning
confidence: 99%